Efficiency of an Optimized Care Organization in Fibromyalgia Patients: The From Intent to Move (FIMOUV) Study Protocol of a Randomized Controlled Trial - Colas, Claire; Goutte, Julie; Creac'h, Christelle; Fontana, Luc; Vericel, Marie-Pierre; Manzanares, Jessica; Peuriere, Marie; Akrour, Madjid; Martin, Charly; Presles, Emilie; Barth, Nathalie; Guyot, Jessica; et al. (Frontiers in Public Health, 2021)
Introduction: Fibromyalgia (FM) is characterized by multiple symptoms including pain, fatigue, and sleep disorders, altering patient's quality of life. In the absence of effective pharmacological therapy, the last European guidelines recommend a multidisciplinary management based on exercise and education. Thus, our main objective was to measure the effectiveness of a healthcare organization offering a specific program of adapted physical activity combined with a therapeutic education program for FM patients. Methods and Analysis: The From Intent To Move (FIMOUV) study will recruit 330 FM patients randomized into two groups: test and control. The test group will benefit from a 1-month mixed exercise training program supervised at the hospital, followed by 2 months in a community-based relay in a health-sport structure. In addition, each of the two groups will benefit from therapeutic patient education sessions. The main endpoint is the measurement of the level of physical activity by accelerometry at 1 year. The secondary endpoints concern adherence to the practice of physical activity, impact on lifestyle, state of health, and physical capacity, as well as an estimate of the budgetary impact of this management strategy. Discussion: This interventional research will allow us to assess the evolution of behaviors in physical activity after an FM syndrome management based solely on patient education or based on a supervised and adapted practice of physical activity associated with this same therapeutic education program. It seems to be the first study evaluating the impact of its intervention on objective data for measuring physical activity and sedentary behavior via accelerometry among FM patients. Trial registration:ClinicalTrials.gov NCT04107948.